REALITAS PEMENUHAN HAK-HAK SIPIL MASYARAKAT ADAT KAMPUNG DUKUH GARUT - Iklilah Muzayyanah D.F.; Kustini Kustini (Harmoni, 2013)
The purpose of this research are understanding the existence of the teaching of Kampung Dukuh Dalam community in Garut and knowing the fulfillment of their civil rights as stated in constitution, UU No. 23, 2006 . This research was conducted using a qualitative approach to data collection, interviews, observation, and study documents data collection, interview, observation and documents review. It was held on April to May 2013 in Cikelet, Ciroyom, Garut District. The results showed that the religious values in Cikelet is still preserved and practiced through reflective actions. The retained values are experiencing dynamics, although the main principles for the perfection of worship is still maintained . In term of their relationship, their position always in unequal position with the people outside. Some issues regarding to civil rights, marriage records, limited health and reproductive health services, etc. One of reason are the lack of law awareness and the lack of socialization from the government.